Cyberterrorism and the News Media - Stuart Macdonald (2014)
This report provides an overview of findings from a research project exploring how mainstream media represent cyberterrorism. The research was conducted in the summer of 2013, and focused on a sample of thirty-one news outlets (selected for reasons of accessibility, language, diversity of geographical origin, and, diversity of political perspective). The report explores news content produced by these 31 outlets between 1 January 2008 and 8 June 2013. These dates were selected because they cover a significant period of time (over five years), during which a number of key events occurred including: the cyberattacks on Georgia, the Stuxnet revelations, and the release of the UK’s Cyber Security Strategy. Items were added to our corpus using a keyword search for the terms “cyber terrorism”, “cyberterrorism” and “cyber terror”, with a total of 535 items identified for coding and analysis.